Ppp6c haploinsufficiency accelerates UV‐induced BRAF(V600E)‐initiated melanomagenesis. Issue 6 (10th April 2021) - Kanazawa, Kosuke; Kishimoto, Kazuhiro; Nomura, Miyuki; Kurosawa, Koreyuki; Kato, Hiroyuki; Inoue, Yui; Miura, Koh; Fukui, Katsuya; Yamashita, Yoji; Sato, Ikuro; Tsuji, Hiroyuki; Watanabe, Toshio; et al.
Abstract: According to TCGA database, mutations in PPP6C (encoding phosphatase PP6) are found in c . 10% of tumors from melanoma patients, in which they coexist with BRAF and NRAS mutations. To assess PP6 function in melanoma carcinogenesis, we generated mice in which we could specifically induce BRAF(V600E) expression and delete Ppp6c in melanocytes. In these mice, melanoma susceptibility following UVB irradiation exhibited the following pattern: Ppp6c semi‐deficient (heterozygous) > Ppp6c wild‐type > Ppp6c ‐deficient (homozygous) tumor types. Next‐generation sequencing of Ppp6c heterozygous and wild‐type melanoma tumors revealed that all harbored Trp 53 mutations. However, Ppp6c heterozygous tumors showed a higher Signature 1 (mitotic/mitotic clock) mutation index compared with Ppp6c wild‐type tumors, suggesting increased cell division. Analysis of cell lines derived from either Ppp6c heterozygous or wild‐type melanoma tissues showed that both formed tumors in nude mice, but Ppp6c heterozygous tumors grew faster compared with those from the wild‐type line. Ppp6c knockdown via siRNA in the Ppp6c heterozygous line promoted the accumulation of genomic damage and enhanced apoptosis relative to siRNA controls. We conclude that in the presence of BRAF(V600E) expression and UV‐induced Trp53 mutation, Ppp6c haploinsufficiency promotes tumorigenesis. Abstract : To assess PP6 function in melanoma carcinogenesis, we generated mice in which we could specifically induce BRAF (V600E) expression and delete Ppp6c in melanocytes. Using these mice, we observed that melanoma susceptibility to UVB irradiation was greatest in Ppp6c semi‐deficient (heterozygous) > Ppp6c wild‐type > Ppp6c‐deficient (homozygous) tumor types, in that order. In the presence of BRAF (V600E) expression and UV‐induced Trp53 mutation, Ppp6c haploinsufficiency promotes tumorigenesis.